The socio-technical organisation of community pharmacies as a factor in the Electronic Prescription Service Release Two implementation: a qualitative study - Harvey Jasmine; Avery Anthony J; Waring Justin; Barber Nick (BMC, 2012)
Abstract Background The introduction of a new method of transmitting prescriptions from general practices to community pharmacies in England (Electronic Prescription Service Release 2 (EPS2)) has generated debate on how it will change work practice. As EPS2 will be a key technical element in dispensing, we reviewed the literature to find that there were no studies on how social and technical elements come together to form work practice in community pharmacies. This means the debate has little point of reference. Our aim therefore was to study the ways social and technical elements of a community pharmacy are used to achieve dispensing through the development of a conceptual model on pharmacy work practice, and to consider how a core technical element such the EPS2 could change work practice. Method We used ethnographic methods inclusive of case-study observations and interviews to collect qualitative data from 15 community pharmacies that were in the process of adopting or were soon to adopt EPS2. We analysed the case studies thematically and used rigorous multi-dimensional and multi-disciplinary interpretive validation techniques to cross analyse findings. Results In practice, dispensing procedures were not designed to take into account variations in human and technical integration, and assumed that repetitive and collective use of socio-technical elements were at a constant. Variables such as availability of social and technical resources, and technical know-how of staff were not taken into account in formalised procedures. Yet community pharmacies were found to adapt their dispensing in relation to the balance of social and technical elements available, and how much of the social and technical elements they were willing to integrate into dispensing. While some integrated as few technical elements as possible, some depended entirely on technical artefacts. This pattern also applied to the social elements of dispensing. Through the conceptual model development process, we identified three approaches community pharmacies used to appropriate procedures in practice. These were 'technically oriented', 'improvising' or 'socially oriented'. Conclusion We offer a model of different work approaches community pharmacies use to dispense, which suggests that when adopting a core technical element such as the EPS2 system of dispensing there could be variations in its successful adoption. Technically oriented pharmacies might find it easiest to integrate a similar artefact into work practice although needs EPS2 to synchronise effectively with existing technologies. Pharmacies adopting an improvising-approach have the potential to improve how they organise dispensing through EPS2 although they will need to improve how they apply their operating procedures. Socially oriented pharmacies will need to dramatically adapt their approach to dispensing since they usually rely on few technical tools.